High prevalence of subnormal testosterone in obese adolescent males: reversal with bariatric surgery. Issue 3 (1st February 2022) - Dhindsa, Sandeep; Ghanim, Husam; Jenkins, Todd; Inge, Thomas H; Harmon, Carroll M; Ghoshal, Amit; Wu, Zengru; McPhaul, Michael J; Saad, Farid; Dandona, Paresh
Abstract: Objective: Obesity in adolescent males is associated with the lowering of total and free testosterone concentrations. Weight loss may increase testosterone concentrations. Design and methods: We evaluated the changes in sex hormones following bariatric surgery in 34 males (age range: 14.6–19.8 years) with obesity. These participants were part of a prospective multicenter study, Teen-Longitudinal Assessment of Bariatric Surgery. The participants were followed up for 5 years after surgery. Total testosterone, total estradiol, luteinizing hormone, follicle-stimulating hormone, sex hormone-binding globulin, C-reactive protein, insulin and glucose were measured at baseline, 6 months and annually thereafter. Free testosterone, free estradiol and HOMA2-IR were calculated. Results: Study participants lost one-third of their body weight after bariatric surgery, with maximum weight loss achieved at 24 months for most participants. Free testosterone increased from 0.17 (95% CI: 0.13 to 0.20) at baseline to 0.34 (95% CI: 0.30 to 0.38) and 0.27 nmol/L (95% CI: 0.23 to 0.32) at 2 and 5 years ( P < 0.001 for both), respectively. Total testosterone increased from 6.7 (95% CI: 4.7 to 8.8) at baseline to 17.6 (95% CI: 15.3 to 19.9) and 13.8 (95% CI: 11.0 to 16.5) nmol/L at 2 and 5 years ( P < 0.001), respectively. Prior to surgery, 73% of the participants had subnormal free testosterone (<0.23 nmol/L). After 2 and 5 years, only 20 and 33%, respectively, had subnormal free testosterone concentrations. Weight regain was related to a fall in free testosterone concentrations. Conclusions: Bariatric surgery led to a robust increase in testosterone concentrations in adolescent males with severe obesity. Participants who regained weight had a decline in their testosterone concentrations.